2022
DOI: 10.1589/jpts.34.360
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to a mild hyperbaric oxygen environment elevates blood pressure

Abstract: This study aimed to investigate the changes in blood pressure due to mild hyperbaric oxygen at 1.3 atmospheres absolute with approximately 30% oxygen. [Participants and Methods] Ten healthy adults participated in two trials: the control (1 atmosphere absolute with 20.9% oxygen) and the mild hyperbaric oxygen (1.3 atmospheres absolute with approximately 30% oxygen) trials. All participants were exposed to either the control or mild hyperbaric oxygen conditions in a chamber for 45 min on each experiment day. [Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…The combined treatment of HBOT and NPH insulin demonstrated not only a beneficial effect on the coronary oxidation status but also positive effects on the cardiodynamics of the isolated rat heart. SLVP and dp/dt max are two cardiodynamic parameters that describe the systolic function, while the parameters dp/dt min and DLVP are related to the diastolic function of the heart; all four mentioned cardiodynamic parameters, as well as CF, were improved in the group of rats treated with the combined treatment (DM+INS+HBOT), which is in accordance with the results of similar studies [ 32 , 33 ]. It has been shown that HBOT induces a slow decrease in HR [ 32 ], but this was not recorded in our research.…”
Section: Discussionsupporting
confidence: 90%
“…The combined treatment of HBOT and NPH insulin demonstrated not only a beneficial effect on the coronary oxidation status but also positive effects on the cardiodynamics of the isolated rat heart. SLVP and dp/dt max are two cardiodynamic parameters that describe the systolic function, while the parameters dp/dt min and DLVP are related to the diastolic function of the heart; all four mentioned cardiodynamic parameters, as well as CF, were improved in the group of rats treated with the combined treatment (DM+INS+HBOT), which is in accordance with the results of similar studies [ 32 , 33 ]. It has been shown that HBOT induces a slow decrease in HR [ 32 ], but this was not recorded in our research.…”
Section: Discussionsupporting
confidence: 90%
“… 19 Consequently, MHOT appears to upregulate parasympathetic tone, leading to decreased HR and enhancing autonomic nervous system balance. 45 SpO 2 , a crucial respiratory circulation parameter, maintained consistent levels across all study time points, with no notable differences observed between groups. This suggests that hyperoxia supplementation might not significantly influence athletes' recovery quality or blood oxygen saturation, potentially hinting at a psychological placebo effect.…”
Section: Discussionmentioning
confidence: 64%
“… 29 However, some reports highlight MHOT's pronounced effect on SpO 2 enhancement, attributed to increased dissolved oxygen levels facilitated by the therapy. 35 , 45 …”
Section: Discussionmentioning
confidence: 99%